Determination of Sexual Harassment and Abuse Women Athletes Face in Sports: A case study, - Yücel, A. S., Korkmaz, M., Karataş, Ö., Hergüner, G., Yaman, Ç., Çatıkkaş, F., (My University, 2014)
Sexual harassment and abuse news are frequent subjects in the written and visual media in our country. In the recent years, sexual harassment and abuse women athletes suffer in sports are frequently brought to agenda. Women are faced with such incidents in sports as in the case of all other surroundings. The main objective of the study was to determine the sexual harassment and abuse women athletes suffer in sports at Fırat University School of Physical Education and Sports and to review the cases in terms of various variables. Target population of the study was made up 280 female students attending to Fırat University School of Physical Education and Sports and research sample is made up of 170 students, who are randomly selected. Questionnaires were conducted on 170 students within the scope of the study. Questionnaire data obtained from the participants were analyz-es using the SPSS 17.0 program. Descriptive statistical methods (Number, Percentage) were used within the scope of the analysis. Chi-square analysis was used in the comparison of the qualitatively categorical variables. As a result of the study, it was found out that 14.7% of the participants suffered from sexual harassment and there was no significant relation between the age, branch and active years of sports and exposure to sexual harassment. Those suffering from sexual harassment stated that they were exposed to sexual harassment by their team mates at the sports halls or fields and most-ly during the trainings and these incidents reduced their performance.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: sports; sexual harass-ment; sexual abuse; woman; train-ing; performance